Management of the mycorrhizal and rhizobial associations to mitigate the negative effects of Grevillea banksii on the development of Dalbergia trichocarpa an endemic tree species - Andrianandrasana Martial Doret; Rondro Harinisainana Baohanta; Herizo Randriambanona; Damase Khasa; Heriniaina Ramanankierana (Asosiasi Mikoriza Indonesia, 2023)
This study aims to improve the development of Dalbergia trichocarpa, a Malagasy native tree species, on a soil invaded by Grevillea banksii, an invasive plant species in eastern part of Madagascar, by inoculating seedlings with mycorrhizal fungal, Rhizophagus irregularis and AMFn strains or rhizobial STM609 and Rn strains, or a mixed rhizobial-mycorrhizal strains. After five months of growth, the results showed that single or dual inoculation boosted significantly the development of D. trichocarpa, compared to control treatments and all parameters measured were markedly different between the time periods of plant invasions. Indeed, the dry mass of aerial biomass was significantly higher in inoculated seedlings than in control seedlings. It was also observed that the number of nodules and the arbuscular mycorrhizal colonization rates of D. trichocarpa increased significantly with inoculated plantlets. However, soil inoculated with the rhizobial strain STM609 alone showed a significantly high global soil microbial activity and the dual inoculation has promoted the soil acid phosphatase activity. These results suggest that dual inoculation with rhizobial and arbuscular mycorrhizal strains was significantly beneficial to the growth, nodulation and mycorrhizal colonization rates of D. trichocarpa in the soil overgrown by G. banksii, an invasive exotic plant species. Thus, this biotechnology can be used for restoration of degraded ecosystems in Madagascar with native tree species.